Large variability in response to projected climate and land‐use changes among European bumblebee species. (16th July 2021) - Prestele, Reinhard; Brown, Calum; Polce, Chiara; Maes, Joachim; Whitehorn, Penelope
Abstract: Bumblebees ( Bombus ssp.) are among the most important wild pollinators, but many species have suffered from range declines. Land‐use change, agricultural intensification, and the associated loss of habitat have been identified as drivers of the observed dynamics, amplifying pressures from a changing climate. However, these drivers are still underrepresented in continental‐scale species distribution modeling. Here, we project the potential distribution of 47 European bumblebee species in 2050 and 2080 from existing European‐scale distribution maps, based on a set of climate and land‐use futures simulated through a regional integrated assessment model and consistent with the RCP–SSP scenario framework. We compare projections including (1) dynamic climate and constant land use (CLIM); (2) constant climate and dynamic land use (LU); and (3) dynamic climate and dynamic land use (COMB) to disentangle the effects of land use and climate change on future habitat suitability, providing the first rigorous continental‐scale assessment of linked climate–land‐use futures for bumblebees. We find that direct climate impacts, although variable across species, dominate responses for most species, especially under high‐end climate change scenarios (up to 99% range loss). Land‐use impacts are highly variable across species and scenarios, ranging from severe losses (up to 75% loss) to considerable gains (up to 68% gain) of suitable habitat extent. Rare species thereby tend to be disproportionally affected by both climate and land‐use change. COMB projections reveal that land use may amplify, attenuate, or offset changes to suitable habitat extent expected from climate impact depending on species and scenario. Especially in low‐end climate change scenarios, land use has the potential to become a game changer in determining the direction and magnitude of range changes, indicating substantial potential for targeted conservation management. Abstract : Climate and land use affect the distribution of pollinators such as bumblebees. We project the future distribution of bumblebees across a range of land use and climate scenarios and disentangle the effects of land use and climate change on future habitat suitability. Direct climate impacts dominate the response for many species in high‐end climate scenarios while land‐use impacts vary widely across species and scenarios. Rare species are disproportionally affected by both climate and land‐use change. Under low‐end climate change, land use may become a critical factor in the future distribution of bumblebees and associated pollination service.